Use of Chemical Tracers in Sus scrofa Population Studies—A Scoping Review - Grzegorz Tarasiuk; Luis G. Giménez-Lirola; Marisa L. Rotolo; Jeffrey J. Zimmerman (Animals)
A highly invasive species, free-ranging Sus scrofa often negatively impact the ecosystem and are capable of spreading a number of impactful pathogens to domestic livestock. Measures taken to ameliorate these impacts and/or control population size are based on the delivery of oral baits containing bioactive chemicals or vaccines, e.g., classical swine fever vaccine. The efficacy of these methods depends on the rate at which inoculated baits are consumed by the pigs. Rhodamine B, tetracycline, and iophenoxic acid are commonly used to quantitate bait uptake in free-ranging pig population studies. All three are effective in this application but differ in fundamental characteristics. When used as a tracer, the effective dose of rhodamine B was established at 15 mg/kg to ensure a 12-week window of detection based on evaluation of hair samples using fluorescent microscopy. Tetracyclines are likewise effective tracers in free-ranging pigs, but the process of detection is highly invasive, i.e., requires euthanasia, and extraction of bone or teeth, followed by examination by fluorescence microscopy. Iophenoxic acid and its derivatives also highly suitable tracers and may be detected in serum for ≥9 months after exposure. Notably tracers used in free-ranging pigs are not suitable for behavioral studies in farm-raised pigs either because the detection method is highly invasive (tetracyclines) or because they are unapproved for use in meat destined for human consumption.